Protection against sexual violence in the colombian legal framework: obstacles and consequences for women victims (2021)
Sexual violence is a type of gender-based violence (GBV), as it is one of the different types of violence that is exerted against women. Sexual violence infringes fundamental human rights, and denies women’s dignity and self-determination, personal development, and well-being. Despite international treaties and a regulatory framework that legally protects Colombian women against sexual violence, it is necessary to know the effectiveness of this regulatory framework in Colombia. Therefore, the main objective of this research is to examine criminal legislation on crimes of sexual violence in Colombia with a dual purpose: first, to analyze procedural guarantees for women victims of sexual violence; second, to determine obstacles for victims of sexual violence in accordance with the legal framework. We used a legal interpretation method to perform an analysis and interpret the law. The results found that, although sexual violence is considered a type of crime, procedural guarantees are not effective as victims encounter serious obstacles with negative consequences, such as the violation of fundamental human rights.